Conquest of Istanbul by Fatih Sultan Mehmet. - Sultonova Makhfuza Ibrokhimovna; Abdugaforov Muhammadkadir (Genius Publishing Group, 2024)
This article deals with the personal life of Sultan Mehmet the Conqueror, the siege of the immortal city, and after this siege, the inhabitants of the city, along with the architecture implemented by the conquistador's descendants, are devoted to the place of Istanbul in the life of Turkey
Keywords: The prophet's prediction about the conquest of Istanbul; Sultan Mehmet the Conqueror